Tran Tren Aplikasi Terjemahan Quillbot: Sebagai Alat Bantu Tambahan Dalam Penerjemahan - Diana Sopha; Teguh Satria Amin; Dian Habibie (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Technology is developing very rapidly in this era where all human activities require the assistance of technology. The existence of technology helps humans in all aspects of life, including translation. The problem with translation is the need for a considerable amount of time if the translation is done manually. However, this problem can be addressed with the presence of the Quillbot application to assist human translation, which can be done quickly, accurately, and practically. Therefore, this Community Service applied using a discussion method socializing the Quillbot application for translation trends to assist humans’ translation. In this case, as an advanced technological product, Quillbot facilitates humans in translating efficiently, practically and quickly. This community service was carried out in Selangor, Universiti Sains Malaysia (USM) through phases of survey, socialization, implementation (training, and discussions) and evaluation. In conclusion, Quillbot Application is very helpful for humans’ translation. It is very necessary, efficient, and practical used to assisst humans’ translation.